Differences in abundance of Thaumatotibia leucotreta and its natural enemies between organic and conventionally farmed citrus ecosystems - Luke Cousins; Mellissa Peyper; Tamryn Marsberg; Sean Moore; Martin Hill (Biological Control)
False codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is endemic to southern Africa and is an important pest in a number of fruit industries, most notably, in the South African citrus industry, as it is considered a phytosanitary pest by many export destinations. Citrus packhouses in South Africa have reported lower infestation of T. leucotreta in fruit from organically farmed orchards than conventionally farmed orchards. Therefore, field surveys were conducted to determine if T. leucotreta infestation was lower on organic citrus farms and to compare natural enemy abundance and species richness between the two farming types. In pheromone trap field surveys, wild adult T. leucotreta numbers were significantly higher in conventionally farmed Palmer Navel and Newhall Navel orange orchards than in matching orchards on neighbouring organic farms. Pitfall trapping recorded significantly higher arthropod generalist predator abundance and species richness in organic farms. Organic orchards had a mean of 7.3 (± 0.6, standard error (SE)) distinct predatory species per trap whereas in conventional orchards 3.9 (± 0.4) species were recorded per trap. Ants, rove beetles, pseudoscorpions and crickets were significantly more abundant in organic orchards. No significant difference was found in spider abundance between organic and conventional citrus orchards. Soil from conventional orchards did not reveal a significantly different incidence of entomopathogenic nematode (EPN) and entomopathogenic fungus (EPF) isolates than the soil from organic orchards. There was, however, a difference between the dominant species in EPF and EPNs in organic and conventional orchard soils. The EPF, Metarhizium anisopliae, was the dominant species in organic soils (81 % of isolates), while Beauveria bassiana was dominant in conventional soils (66 % of isolates). Of the few EPN isolates obtained, the majority in conventional soils (87 %) were Heterorhabditis zealandica, while in organic soils the majority (75 %) were identified to be H. bacteriophora. The findings of this study provide evidence for reduced T. leucotreta infestation in organic citrus orchards, suggesting increased generalist predator abundance as a possible contributing factor.